PERKEMBANGAN PONDOK PESANTREN PEMBANGUNAN PULAU PUNJUNG KABUPATEN DHARMASRAYA 1952-2004 - Rahman, Yeni; Kaksim, Kaksim; Nazmi, Ranti (Pendidikan Sejarah, 2013)
ABSTRACTÂ This thesis study about the development Muslim Boarding School Pembangunan Pulau Punjung Kabupaten Dharmasraya (1952-2004). The wole problem in this thesis is about the history, condition, development and the factors that influence of the development of muslim boarding school Pembangunan Pulau Punjung. In generally the purpose of this research is to uncover the educationâs development of muslim boarding school Pembangunan Pulau Punjung since 1952 until 2004, mean while the specific purpose is to describe the development of muslim boarding school Pembangunan Pulau Punjung since 1952-2004. The method of this research is the history method which the phases below, heuristic is collectiy the data. Interpretation is master about meaning and interpretation of the information that has collected, then historiografi is writing theÂ  result of the research in scientific writing or thesis. The result of this research is the establisment Muslim boarding school Pembangunan Pulau Punjung motivated by the desire Hj. Rawiyana after she graduated her education in one of the school at Bukittinggi, that is Madrasah Tarbiyah Islamiyah to establish a school that Islamic. The purpose is to help the society to solved the problem in education. In 1952, Muslim Boarding School named Madrasah Tarbiyah Islamiyah with non formal education. In 1966 changed be Islamic of junior high school. In 1969 that establish of PGA, in 1978 PGA changed be MTS and MA and in 1983 establish the institute of Muslim Boarding School Pembangunan Pulau Punjung. In itâs development of muslim boarding school Pembangunan Pulau Punjung, in part of education although in buildings can not separate of help from the religion department, the foundation of Amal bakti Muslim Pancasila, society, and the leader of muslim boarding school. Mean While the leader of muslim boarding school processes and manage so that the education and the buildings of muslim boarding school can run well like a institute of religion education that famous by society.Â Keywoard: Development, Muslim Boarding School, Pulau Punjung, Dharmasraya